Perinatal complications and long-term neurodevelopmental outcome of infants with intrauterine growth restriction - von Beckerath, Anne-Karen; Kollmann, Martina; Rotky-Fast, Christa; Karpf, Eva; Lang, Uwe; Klaritsch, Philipp (American journal of obstetrics and gynecology, 2013)
The objective of the study was to evaluate perinatal and long-term complications of fetuses with intrauterine growth restriction (IUGR) compared with constitutionally small for gestational age (SGA) ones. The outcome of infants with IUGR and SGA born at the Medical University Graz (Austria) between 2003 and 2009 was retrospectively analyzed. Group assignment was based on birthweight, Doppler ultrasound, and placental morphology. The primary outcome was neurodevelopmental delay at 2 years corrected age. The secondary outcomes were perinatal complications. We included 219 IUGR and 299 SGA infants for perinatal and 146 and 215 for long-term analysis. Fetuses with IUGR were delivered earlier (35 vs 38 weeks) and had higher rates of mortality (8% vs 1%; odds ratio [OR], 8.3) as well as perinatal complications (24.4% vs 1.0%; OR, 31.6). The long-term outcome was affected by increased risk for neurodevelopmental impairment (24.7% vs 5.6%; OR, 5.5) and growth delay (21.2% vs 7.4%; OR, 3.4). IUGR infants are subject to an increased risk for adverse short- and long-term outcome compared with SGA children.